Life Insurance Protection for High-Risk Occupations for State Civil Apparatus - Mulyadi, Muhamad Budi; Astuti, Hesti Dwi; Sukarman , Yuliana Salwa (Yayasan Studi Cendekia Indonesia (YSCI), 2023)
The government has an obligation to provide Work Accident Insurance (JKK) and Death Insurance (JKM) protection to the State Civil Apparatus (ASN). This aims to improve the welfare of ASN, in addition to providing life insurance protection for high-risk jobs for ASN. The research method used is normative juridical, which is to study and examine legal principles, especially positive legal principles derived from existing literature materials from laws and regulations. The results showed that the excellent services provided by the police to the community include security maintenance, protection, protection, and law enforcement, in accordance with Article 13 of Law Number 2 of 2002 concerning the Indonesian National Police. Police work in Indonesia carries risks and workloads that can cause stress, with stressors including excessive workload, time pressure, poor quality executives, unfavourable political climate, inadequate authority, prolonged conflict, differences in task values between leaders and subordinates, and unusual organisational changes. In addition, the results of the study state that PT ASABRI (Persero) is a State-Owned Enterprise responsible for managing social insurance programs for TNI Soldiers, members of the National Police, and State Civil Apparatus Employees (ASN) within the Ministry of Defence and the National Police, in accordance with Government Regulation Number 102 of 2015 concerning Social Insurance for Soldiers of the Indonesian National Army, Members of the Indonesian National Police, and State Civil Apparatus Employees within the Ministry of Defence and the National Police of the Republic of Indonesia.